Implementation of the ANP method to overcome delays panel box raw materials in PT. Agrivito - Dwi Jayawan; Ribangun Bamban Jakaria (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Choosing raw material suppliers is one of the most crucial elements. If the raw materials supplied by the supplier are of poor quality, this will affect the quality of the product produced. If suppliers are unable to provide raw materials, production schedules will be disrupted and the company will not succeed in achieving its vision. PT. A is a company that produces electrical panel boxes. In making a box, raw materials are needed, namely sheet metal for all parts of the box shape. The raw material system at PT. A experienced problems with delays in raw materials so that the production process did not run smoothly, PT. GC, PT. SSL and PT. SIPA is the supplier that provides the raw material for the plate. This has a direct impact on the smooth production of the company. This research aims to supply raw materials from the three companies smoothly by selecting one company that to supply according to PT's needs. A. The method used in this research is the Analytic Network Process (ANP) method. Selection of raw material suppliers involves 6 criteria, 12 sub-criteria, and 3 alternative suppliers. The results of the calculation of the Analytic Network Process (ANP) method with the three best alternative suppliers based on the highest weight, PT SIPA obtained sub-criteria scores including ease of negotiation (0.63484), accuracy of quantities (0.63699), meeting sudden requests (0.63699), on-time delivery (0.63699), providing guarantees (0.66942), speed of responding to complaints (0.63699), and ability to respond to requests (0.63699). Meanwhile, PT GC excelled in the sub-criteria of meeting the increasing number of requests (0.73065), payment method (0.37129), free from physical contamination (0.73065), conformity to specifications (0.63699), and ease of communication (0.66942). Meanwhile for PT. SSL does not have the highest sub-criterion